DRIVING THE MINORITY AND MAJORITY INTERRELIGIOUS RELATIONS IN BALI - Titin Nurhidayati; Muhammad Bahrul Ula (Al'Adalah, 2022)
This study aims to determine the various factors that shape the harmonious relationship between Muslims and Hindus in Bali. The locus of this research is Jimbaran Village, South Kuta District, Badung Regency, Bali Province. This study uses a qualitative research methodology with a narrative descriptive analysis approach and is included in the type of literature study research. The results of this study indicate that the pattern of social relations between Muslims and Hindus in Bali is not only formed based on the understanding of their respective religious teachings, but it can also be shaped by customs in Balinese society and shaped by several factors that influence it. Five factors shape the harmonization of social relations between Muslims and Hindus in Bali, including the conflicts between Muslims and Hindus in Bali, the competition between Muslims and Hindus in Bali, and adjustments made by Muslims to Hindus in Bali, tolerance and cooperation among Muslims in Bali.